Employee Creativity and Organisational Support as Strategic Human Resources: A Resource-Based View of Job Satisfaction in Vocational Higher Education - Arif Agus Fajar Riyanto; Dewi Prihatini; Markus Apriono; Ni Made Widnyani; Salehuddin Widnyani; Erin Nur Putriani (Media Manajemen Pendidikan, 2026)
This study examines the influence of employee creativity and perceived organizational support on job satisfaction among civil servant educators at Banyuwangi State Polytechnic, Indonesia. Guided by the Resource-Based View (RBV), we conceptualize employee creativity as a valuable, rare, and inimitable human resource that, when coupled with organizational support mechanisms, enhances job satisfaction. A quantitative design was employed, with data collected from 138 educators and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Results demonstrate that both employee creativity (β = 0.412, p < 0.01) and perceived organisational support (β = 0.387, p < 0.01) significantly and positively influence job satisfaction. The findings support RBV propositions that creativity, when supported by the organization, can foster sustainable competitive advantage by enhancing employee satisfaction. This study advances RBV literature by demonstrating how intangible human resources and organizational capabilities function as complementary strategic assets in educational contexts. It provides novel insights for managing human resources in resource-constrained vocational institutions.